The Growth of a Craft Labour Force: Montreal Leather Artisans, 1815‑1831 - Burgess, Joanne (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1988)
AbstractThis study calls into question the view that immigration from the British Isles in the firsthalf of the nineteenth century dramatically altered the ethnic composition of the urbancrafts of Lower Canada and resulted in the marginalisation of French-Canadianartisans.Unlike earlier studies, which relied essentially on the snapshots provided by themanuscript censuses of 1831 and 1842, this case study combines a variety of sources inorder to reconstitute the entire population of Montreal's leather trades between 1815 and1831. The evidence provided by this important group of crafts shows that, while theBritish presence increased, it was primarily confined to the most transient elements of theanisan population. A mong craftsmen who settled in Montréal for extended periods oftime, French Canadians remained dominant. Although their relative importancedeclined, their absolute numbers grew. Vital craft traditions ensured that skills weretransmitted from father to son and that apprenticeship thrived. While the local ecomonywas the major source of new manpower throughout this period, there was a steadyincrease in the flow of young men into Montréal from the surrounding countryside.